2007
DOI: 10.3748/wjg.v13.i18.2523
|View full text |Cite
|
Sign up to set email alerts
|

Magnifying chromoscopy, a novel and useful technique for colonoscopy in ulcerative colitis

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel disorder characterized by exacerbations and remissions. The degree of inflammation as assessed by conventional colonoscopy is a reliable parameter of disease activity. However, even when conventional colonoscopy suggests remission and normal mucosal findings, microscopic abnormalities may persist, and relapse may occur later. Patients with long-standing, extensive ulcerative colitis have an increased risk of developing colorectal cancer. Ulcerative coliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…In addition, high‐resolution images are now able to distinguish minute changes to the mucosal condition. Progress in the development of endoscopic instruments, and the arrival of sophisticated technology, have made it possible to observe minute features of bowel inflammation in UC 15. Hence, high‐resolution, still endoscopic images now permit us to categorize disease activity into more than 4 levels of severity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high‐resolution images are now able to distinguish minute changes to the mucosal condition. Progress in the development of endoscopic instruments, and the arrival of sophisticated technology, have made it possible to observe minute features of bowel inflammation in UC 15. Hence, high‐resolution, still endoscopic images now permit us to categorize disease activity into more than 4 levels of severity.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, target biopsies of suspicious lesions might provide more effective surveillance than taking random biopsies. [28][29][30] Hurlstone et al 31,32 reported on the efficacy of magnifying colonoscopy in UC using ''optical biopsy'' for the surveillance of colitic cancer and disease extent. Nishizawa et al 33 first reported the healing process patterns of UC mucosa using the feature of magnifying colonoscopy.…”
Section: Histological Findingsmentioning
confidence: 99%
“…Random biopsy protocols have been documented to take longer than standard endoscopic procedures; ideally, methods to target biopsies could enhance the diagnostic yield while limiting the duration of the procedure. Both indigo carmine and methylene blue (42), combined with magnification endoscopy (43,44), have been shown in 'back-to-back' tandem endoscopies (conventional versus chromoendoscopy) to improve detection of dysplasia while limiting the number of biopsies. Narrow band imaging (NBI) (45,46) has also been evaluated in a similar manner, with lesion patterns described (47).…”
Section: Methods To Enhance Detection Of Dysplasia In Colitismentioning
confidence: 99%